2017
DOI: 10.1016/j.jtho.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Biomarker Expression by Osimertinib: Results of the Paired Tumor Biopsy Cohorts of the AURA Phase I Trial

Abstract: Collection of paired biopsy samples was challenging because of rapid tumor regression after osimertinib treatment, highlighting the difficulties of performing on-study biopsies in patients treated with highly active drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…The overall T790M positive rate was 52.2% considering all testing methods, the ORR of T790M positive patients receiving osimertinib treatment was 60.9%. These data were similar compared with published data [ 7 , 9 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…The overall T790M positive rate was 52.2% considering all testing methods, the ORR of T790M positive patients receiving osimertinib treatment was 60.9%. These data were similar compared with published data [ 7 , 9 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the role of the tumor microenvironment in modulating tumor evolution, is also gaining interest, particularly with respect to immune cell infiltration. Paired biopsies from the AURA1 trial of osimertinib, demonstrated the significant increased immune cell infiltrate (particularly CD8+ cells) associated with therapy [35]. Unfortunately, an early trial of combination osimertinib with durvalumab was suspended due to high rates of interstitial lung disease, much greater than would be expected with either agent alone [36].…”
Section: Therapeutic Targeting Of Persistencementioning
confidence: 99%
“…In the phase I AURA trial, 60 patients with the EGFR mutation (only 23% with the T790M mutation) received 80 or 160 mg/day osimertinib treatment. The ORR was 67% and 87%, and PFS was 22.1 and 19.3 months, respectively [ 39 ]. These results are more in line with the efficacy of erlotinib or afatinib in the first line, indicating that osimertinib can serve in the first-line treatment for NSCLC.…”
Section: Acquired Resistance and Corresponding Strategiesmentioning
confidence: 99%